Copper-chromium alloy as a superior electrode material for electrical discharge machining of die steels. (1st January 2012) - Kumar, Sanjeev
Electrical discharge machining (EDM) is widely used for the machining of accurate profiles in dies and press tools which have been previously hardened. Electrode material properties significantly affect the output process parameters. This paper investigates the performance of copper-chromium alloy with copper and brass as EDM electrode materials. It has been found that copper-chromium alloy gives higher material removal rate, superior surface finish, better micro-hardness and least overcut (good dimensional accuracy). At the same time, its tool wear rate is lower which results in better accuracy and trueness of the machined profiles. Scanning electron microscope (SEM) image after machining with this electrode material shows a smoother surface with smaller asperities. Energy dispersive spectroscopy (EDS) analysis of the machined surfaces reveals the presence of electrode constituents and indicates surface alloying by EDM process.